Spirituality-religious techniques is an effective intervention for improvement coping strategy in women with breast cancer in Iran - Shahrbanoo Ghahari; Saeed Imani; Nooshin Khademolreza (Shahid Beheshti University of Medical Sciences, 2018)
Breast cancer is the most common type of cancer among women in the world, which this is a serious problem in many developing countries. In the world we can anticipate prevalence of cancer will high to double by 2020 and this news is very important issue for health care and women (1) .In Iran breast cancer is common among women representing 22.4% in 100000 women (2). cancer can have many negative psychological consequences such as depression ,sexual relationship problem, problem with significant others especial husband and children, isolation, low self-esteem, anxiety, worry about  future and health, hopelessness and helplessness, suicidal ideation, negative body image and self-blaming which affect their illness (3 ). Therefore, coping with this disease is an important challenge for patients.